Literatur Review Management Analysis of Medical Record Management System in Puskesmas - Kohar, M Yusuf (RADINKA JAYA UTAMA PUBLISHER, 2024)
The medical record management system at the community health center level is the same as the hospital medical record management system. This study aims to determine the management of the medical record system in health centers. This study is a literature review using methods of traditional review to seek, identify, evaluate, and interpret theoretical references relevant to the management of medical record systems in public health centers. The numbering system used in the health center is the Unit Numbering System, The medical record naming system uses a direct naming system, a centralized medical record document storage system at the health center, and a medical record document alignment system at the health center, namely a direct number alignment system and alignment system per region area. According to alphabetical order, assembly activities have not been carried out properly because there is no standard operating procedure for their implementation. The coding implementation at the community health centers did not use the ICD-10 book as a guideline for providing disease codes, the community health centers did not have a fixed retention schedule, so the retention and destruction of medical record documents at the community health centers had not been implemented. Conclusion: The numbering and naming system implemented at the community health centers is inappropriate, and the implementation of the medical record data processing system at the community health centers has not been optimal.